Pengaruh Servant Leadership, Resistance To Change, dan Organizational Commitment Terhadap Organizational Citizenship Behavior (OCB) pada Karyawan PT. Telekomunikasi Selular Regional Jawa Tengah & DIY - Nuraisyah Ramadhani Putri; Suhana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The objective of this research is for analyze also evaluate the effect of servant leadership, resistance to change, and organizational commitment on organizational citizenship behavior (OCB) of PT. Telekomunikasi Selular Regional Jawa Tengah & DIY. The population on this research is 148 permanent employees and there were 110 respondents with convenience sampling. The data result was collected by questionare with 5 point of likert scale. The examine uses multiple linear regression technique by SPSS software version 16. The research outcome represented that servant leadership had positive affect also significant affect on OCB in PT. Telekomunikasi Selular Regional Jawa Tengah & DIY. Beside that organizational commitment had positive affect also significant affect on (OCB) PT. Telekomunikasi Selular Regional Jawa Tengah & DIY. Meanwhile resistance to change had no affect on OCB in PT. Telekomunikasi Selular Regional Jawa Tengah & DIY. PT. Telekomunikasi Selular is a telecommunications company and there are always innovation related to telecommunication technology, so that it is not support with resistance to change.